z-1=1+5i-z

Simple and best practice solution for z-1=1+5i-z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-1=1+5i-z equation:


Simplifying
z + -1 = 1 + 5i + -1z

Reorder the terms:
-1 + z = 1 + 5i + -1z

Solving
-1 + z = 1 + 5i + -1z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add 'z' to each side of the equation.
-1 + z + z = 1 + 5i + -1z + z

Combine like terms: z + z = 2z
-1 + 2z = 1 + 5i + -1z + z

Combine like terms: -1z + z = 0
-1 + 2z = 1 + 5i + 0
-1 + 2z = 1 + 5i

Add '1' to each side of the equation.
-1 + 1 + 2z = 1 + 1 + 5i

Combine like terms: -1 + 1 = 0
0 + 2z = 1 + 1 + 5i
2z = 1 + 1 + 5i

Combine like terms: 1 + 1 = 2
2z = 2 + 5i

Divide each side by '2'.
z = 1 + 2.5i

Simplifying
z = 1 + 2.5i

See similar equations:

| -11+y=13-y | | 5n-9=2n+12 | | x^3+16x=10x^2-80 | | 3/7a=0.6 | | 11t-14=95-16t | | 2+3p-2-4p+7= | | 33+45-(3*9)=x | | 7.57x+49.72=80 | | 5+2(x+2)=12 | | x^3-10x^2+16x+80=0 | | 5(x-7)-3x=4(x-1)-1 | | 3x-4x-8x=10x-8 | | 4x-4+2y=0 | | (x+4)(3x-4)=448 | | 9h+4-7=14 | | 5+0.09x=13.19 | | (x-2)(x-4)(x-6)=40x | | 5+9x=13.19 | | P=4x+36 | | 7c-(8)-(2c)=17 | | 3.2(x+4)+2.7x=5.4(x+2) | | 2/13, | | 3x-7=4(2-x)-1 | | 7c-8-2c=8 | | 0=4800-560x+12x^2 | | 4z-6=(6z+2) | | 12x^2-150+x=0 | | 6+4x+1-2x=-7+3x+9-2x | | 7c+4d-c-3d= | | (1.2*10^-2)=(x^2)/(0.01-x) | | 22-3f=15m | | P(t)=-t^4+72t^2+225 |

Equations solver categories